Digitalization as one of trends of transport and logistics development in modern conditions - E. N. Rudakova; A. I. Panshin; A. V. Vlasov (Путеводитель предпринимателя, 2021)
Life does not stand still, it is constantly evolving. Digitalization has affected absolutely all spheres of human activity, especially in various industries. The transport and logistics area was no exception, which every year is more and more susceptible to this phenomenon. The article analyzes the trends in the development of transport and logistics in the context of digitalization.